A review of the effects of crop agronomy on the management of Alopecurus myosuroides. (3rd June 2013) - Lutman, P J W; Moss, S R; Cook, S; Welham, S J
Summary: This study reviews 52 field experiments, mostly from the UK, studying the effects of cultivation techniques, sowing date, crop density and cultivar choice on Alopecurus myosuroides infestations in cereal crops. Where possible, a statistical meta‐analysis has been used to calculate average responses to the various cultural practices and to estimate their variability. In 25 experiments, mouldboard ploughing prior to sowing winter cereals reduced A. myosuroides populations by an average of 69%, compared with non‐inversion tillage. Delaying drilling from September to the end of October decreased weed plant densities by approximately 50%. Sowing wheat in spring achieved an 88% reduction in A. myosuroides plant densities compared with autumn sowing. Increasing winter wheat crop density above 100 plants m −2 had no effect on weed plant numbers, but reduced the number of heads m −2 by 15% for every additional increase in 100 crop plants, up to the highest density tested (350 wheat plants m −2 ). Choosing more competitive cultivars could decrease A. myosuroides heads m −2 by 22%. With all cultural practices, outcomes were highly variable and effects inconsistent. Farmers are more likely to adopt cultural measures and so reduce their reliance on herbicides, if there were better predictions of likely outcomes at the individual field level.